The next 100 years : a forecast for the 21st century - Friedman, George (Allison & Busby, 2010)
The New York Times Bestseller If you think you know where the world is headed, think again Mexico making a bid for global supremacy? Poland becoming America's closest ally? World War III taking place in space? It might sound fantastic but all these things can happen. In The Next 100 Years, George Friedman, author of the huge bestseller America's Secret War offers a lucid, highly readable forecast of the changes we can expect around the world during the 21st century. He predicts where and why future wars will erupt, and how they will be fought; which nations will gain and lose economic.- Resumé vydavatel
Keywords: světová politika -- prognózy -- 21. století; mezinárodní vztahy -- prognózy -- 21. století; world politics -- forecasting -- 21st century; international relations -- forecasting -- 21st century; elektronické knihy; populárně-naučné publikace; electronic books; popular works